PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA MELALUI PENERAPAN MODEL DISCOVERY LEARNING DI SMP NEGERI 1 SUNGAI AUR - Kartini, Kartini; Hutapea, Nahor Murani; Nur’azani, Alifya (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research caused by the low ability of mathematical understanding’s students in junior high school 1 sungai aur. The aim of study was to count improvement of mathematical understanding’s students ability through discovery learning model The research method was experimental study with non equivalen pretest and posttest control group design. The population of this study was all of the students from grade junior high school 1 Sungai Aur. The subject was divided into two groups, 8th-7 as experiment group and 8th-6 as control group.. The research instruments was essay questions mathematical understanding ability. The result shown that mathematical understanding’s students through discovery learning model which is classified as moderate. In other way, the mathematical understanding’s student through convensional model has means classified as low. As a conclude, mathematical understanding’s students through discovery learning was better than the conventional one.Key Words: Discovery Learning, Mathematical Understanding Ability.